2008
DOI: 10.1037/0022-0663.100.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of children's academic competence from their effortful control, relationships, and classroom participation.

Abstract: The authors examined the relations among children's effortful control, school relationships, classroom participation, and academic competence with a sample of 7-to 12-year-old children (N = 264). Parents and children reported on children's effortful control, and teachers and children reported on children's school relationships and classroom participation. Children's grade point averages (GPAs) and absences were obtained from school-issued report cards. Significant positive correlations existed between effortfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
318
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(363 citation statements)
references
References 84 publications
34
318
3
8
Order By: Relevance
“…This effect was found above and beyond other predictors such as receptive vocabulary and teacher-child closeness and conflict. Previous longitudinal research has reported a negative effect of a lack of independent classroom participation on the development of cognitive competencies and achievement, suggesting that the cognitive development of these children is at risk (Bossaert et al, 2011;Ladd et al, 1999;Valiente et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was found above and beyond other predictors such as receptive vocabulary and teacher-child closeness and conflict. Previous longitudinal research has reported a negative effect of a lack of independent classroom participation on the development of cognitive competencies and achievement, suggesting that the cognitive development of these children is at risk (Bossaert et al, 2011;Ladd et al, 1999;Valiente et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence that the association between self-regulation and course grades is mediated by ef ective study habits, ef ort, and prosocial behavior in the classroom (Cred é & Kuncel, 2008;Duckworth & Seligman, 2005 Note. Associations were reported in a meta-analysis by Poropat ( 2009 Lemery-Chalfant, & Castro, 2007 ;Valiente, Lemery-Chalfant, Swanson, & Reiser, 2008 ). h ere is increasing evidence to suggest that the path of school success is set at a tender age.…”
Section: High School Completionmentioning
confidence: 99%
“…Temperament has been examined in relation to, for example, students' achievement, student-teacher interactions, problem behavior, and psychosocial functioning at school (e.g., Eisenberg et al, 2009;Nelson, Martin, Hodge, Havill, & Kamphaus, 1999;Valiente, Lemery-Chalfant, & Swanson, 2010;Zhou, Main, & Wang, 2010). For example, studies among kindergartners and elementary school students have found good self-regulation or high effortful control to be positively related to students' self-efficacy (Liew, McTigue, Barrois, & Hughes, 2008), academic competence (Liew et al, 2008;Valiente et al, 2010;Zhou et al, 2010), classroom participation (Valiente, Lemery-Chalfant, Swanson, & Reiser, 2008), school liking (Valiente, Lemery-Chalfant, & Castro, 2007), and work habits (Curby, Rudasill, Edwards, & Pérez-Edgar, 2011). Kindergarten and elementary school students' shyness or behavioral inhibition, TEMPERAMENT, AFFECTS, AND BEHAVIORS 6 on the other hand, has been shown to be negatively related to their academic engagement (Hughes & Coplan, 2010) and achievement (Hughes & Coplan, 2010;Valiente et al, 2010).…”
Section: Temperament In the School Contextmentioning
confidence: 99%